Planning and Mapping of Lunjen Village, Buntu Batu District, Enrekang Regency - Firda Rahmayanti; Farid Asfari Rahman; Regina Shintya Dewi J; Mas Dadang Enjat Munajat; Evi Novianti (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2023)
This study aims to determine tourist attractions and to design a mapping model for the distribution of tourist attractions and amenities in Lunjen Village, Enrekang Regency by making a map of tourist attractions and amenities in Lunjen Village. This study uses a qualitative descriptive research design that aims to describe and describe the phenomena studied. This research model is applied with the aim of obtaining a result that can be implemented for tourism development in Lunjen Village. Data collection was carried out through direct observation in the field accompanied by unstructured interviews and documentation. The results of the study are maps of the distribution of tourist attractions and amenities in Lunjen Village using ArcGIS 10.8, which is used as a media aid for tourists in obtaining information about tourist attractions in Lunjen Village, Enrekang Regency. The conclusion in this study is the distribution of tourist attractions using ArcGIS 10.8 can make it easier to see tourist attractions and amenities in Lunjen Village in the form of a map. Tourism development is expected to reach a development scale that is considered clear and good in terms of tourism planning, development and management. In order to create good management, it is necessary to involve the community in tourism planning and development in Lunjen Village, Enrekang Regency